Alkalizing activity, setting time, and infrared spectroscopy of mineral trioxide aggregate mixed with platelet concentrates: An in vitro study - Shaymaa Shakir Hassan; Emad Farhan Alkhalidi; Rayan Salim Hamed (Saudi Endodontic Journal)
Introduction: Platelet concentrates are gaining significant interest in various fields of dentistry due to their biocompatibility and growth factors release, and their effect on the properties of pulp capping material is important to examine; therefore, this study aimed to investigate the effect of injectable platelet-rich fibrin (I-PRF) and platelet-rich plasma (PRP) as a mixing liquid instead of distilled water on the alkalizing activity (pH), setting time, and chemical behavior of mineral trioxide aggregate (MTA). Materials and Methods: ProRoot MTA was used; this study included three groups according to mixing medium as follows: G1: MTA + I-PRF; G2: MTA + PRP; and G3: MTA + distilled water (control). The pH change of each group (n = 8 per group) was assessed at various immersion times (1 day, 7 days, 14 days, and 28 days). The setting time for each group (n = 5 per group) was evaluated using a Gilmore needle. The chemical behavior of each group was evaluated using Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR). pH data and setting time were analyzed statistically using analysis of variance and Tukey’s tests. Results: All tested groups created an alkaline pH at all immersion periods, while the pH gradually and significantly (P < 0.05) decreased over successive immersion times. I-PRF and PRP groups showed significantly (P < 0.05) higher pH values than the water group at 1 day, 7 days, and 14 days while there was no significant difference among groups at 28 days. For setting time, the I-PRF group showed significantly (P < 0.05) higher setting time than the water group, but no significant difference in the setting time between the PRP group and the water group. The ATR-FTIR spectroscopic analysis demonstrated the formation of hydration byproducts when I-PRF and PRP were used instead of distilled water. Conclusions: I-PRF and PRP, when used as a mixing liquid for MTA, promoted an alkaline pH, allowed the setting of ProRoot MTA, and resulted in the formation of the typical hydration reaction byproducts.